19
Аноним
Математика
15 января 12:45

Преобразуйте в многочлен выражение: (-m+n)³= (-2+k)³= (-x-y)³= (-0,5+p)³=

Ответ или решение1

1 ) ( - m + n ) ^ 3 = ( n - m ) ^ 3 = n ^ 3 - 3 * n ^ 2 * m + 3 * n * m ^ 2 - m ^ 3;
2 ) ( - 2 + k ) ^ 3 = ( k - 2 ) ^ 3 = k ^ 3 - 3 * k ^ 2 * 2 + 3 * k * 2 ^ 2 - 2 ^ 3 = k ^ 3 - 6 * k ^ 2 + 12 * k - 8;
3 ) ( - x - y ) ³ = - ( x + y ) ^ 3 = - x ^ 3 - 3 * x ^ 2 * y - 3 * x * y ^ 2 - y ^ 3;
4 ) ( - 0 , 5 + p ) ³ = ( p - 1 / 2 ) ^ 3 = p ^ 3 - 3 * p ^ 2 * 1 / 2 + 3 * p * ( 1 / 2 ) ^ 2 - ( 1 / 2 ) ^ 3 = p ^ 3 - 3 / 2 * p ^ 2 + 3 * p * 1 / 4 - 1 / 8 = p ^ 3 - 3 / 2 * p ^ 2 + 3 / 4 * p - 1 / 8.
0 / 10000
ВходРегистрация

Вход

или

Регистрация